Organic vs Conventional Management in Cassava: Growth Dynamics, Yield and Soil Properties - Seena Radhakrishnan, A R; Girija, Suja; Anil, Anish T. (JOURNAL OF ROOT CROPS, 2015)
Worldwide concerns regarding the food safety, anthropogenic degradation of the environment and the threats to human health have generated interest in sustainable alternative agricultural systems like organic farming. Cassava is a food and nutritional security crop with immense industrial uses. Lack of package of practices recommendations for organic production hinders the promotion of organic farming. Hence a field experiment was laid out during 2011 and 2012 in split plot design with three varieties, H-165, SreeVijaya and Vellayani Hraswa in main plots and five production systems, traditional, conventional, integrated and two types of organic in sub plots at Central Tuber Crops Research Institute, Thiruvananthapuram, India, to develop technologies for organic production of cassava. Growth attributes and the phasic course of biomass production and partitioning to various plant parts were favoured under organic farming. Crop growth rate of cassava remained steady under organic management. Relative growth rate and tuber bulking rate at the mid and final phases and leaf area index and mean tuber bulking rate were seen promoted in organic practice. Organic management enhanced yield by 8% over conventional practice. At the end of second year, the pH was significantly higher and tended towards neutrality in the organic practice (5.864) and organic C status was raised by 9.5% over the conventional system. There was no significant difference in the status of available N, P and K (after second crop) or secondary and micro nutrients (after first crop). However, exchangeable Ca, Mg, Fe, Cu and Zn were slightly favoured under organic practice.The study indicates that organic management, which advocates eco-friendly technologies, was equally good as that of conventional practice. Technologies for organic production were standardized.<!–?xml:namespace prefix = "o" ns = "urn:schemas-microsoft-com:office:office" /–>